1999
DOI: 10.1046/j.1469-1809.1999.6330227.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variants in the 5′ flanking region of the leptin gene are associated with obesity in women

Abstract: Few mutations have been found in the human leptin gene and the relationship between leptin gene sequence variation and human overweight is uncertain. To determine whether sequence variation within the leptin gene and its regulatory elements contribute to extreme obesity, we screened " 3 kb of the 5h flanking region and the three exons in 125 unrelated extremely obese (BMI 40 kg\m#) and 86 average weight women (BMI 27 kg\m#). Within the protein coding regions only one heterozygous silent mutation was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
2
8

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 0 publications
10
71
2
8
Order By: Relevance
“…[17][18][19][20][21][22] Because some studies used either small and/or selected samples and the criteria utilized to classify cases and controls differed largely, the relation between this SNP and type 2 diabetes Common SNPs in LEP and LEPR NY Souren et al and/or obesity is still unclear. Our data suggest that the LEP 19G4A SNP may be protective against cardiovascular disease, as G allele carriers have significantly higher HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22] Because some studies used either small and/or selected samples and the criteria utilized to classify cases and controls differed largely, the relation between this SNP and type 2 diabetes Common SNPs in LEP and LEPR NY Souren et al and/or obesity is still unclear. Our data suggest that the LEP 19G4A SNP may be protective against cardiovascular disease, as G allele carriers have significantly higher HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we therefore examined the effect of common SNPs in LEP and LEPR on birth weight and adult metabolic risk factors for type 2 diabetes measured in young twins recruited from the East Flanders Prospective Twin Survey (EFPTS). The SNPs studied have previously been associated with type 2 diabetesrelated traits in other populations, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and are either nonsynonymous or located in a region that might be of importance in the regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of measured plasma levels before the diagnosis of NHL, long-term variation in production of these adiponectins may be indicated by the polymorphisms investigated here, since the LEP 19G, LEP À2548A and LEPR 223R alleles have been associated with elevated leptin levels, and the APM1 276T allele with lower adiponectin levels (Hoffstedt et al, 2002;van Rossum et al, 2003;Filippi et al, 2004). Further, these polymorphisms have been linked with an obese phenotype in some Caucasian populations (Li et al, 1999;Mammes et al, 2000;Quinton et al, 2001;Yiannakouris et al, 2001;Nieters et al, 2002;Filippi et al, 2004;Jiang et al, 2004). Previously, Skibola et al (2004) reported that, relative to the LEP 19AA genotype, carriers of the LEP 19G allele were at increased risk of NHL, particularly FL (OR ¼ 1.9, 95% CI 1.0 -3.6).…”
Section: Discussionmentioning
confidence: 85%
“…150 A common A4G 5 0 UTR variant in the leptin gene has been associated with leptin levels and obesity. 152,153 In the 5 0 region, GÀ2548A has been associated with response to low calorie diet, obesity and leptin levels. [153][154][155][156][157] Furthermore, a leptin gene 3 0 -tetranucleotide repeat is associated with BMI.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
“…152,153 In the 5 0 region, GÀ2548A has been associated with response to low calorie diet, obesity and leptin levels. [153][154][155][156][157] Furthermore, a leptin gene 3 0 -tetranucleotide repeat is associated with BMI. 158 Finally, in the most extensive study of leptin gene polymorphisms in common obesity, common variants further upstream in the 5 0 region have displayed association with BMI.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%